Biomimetic mineralized collagen membrane, preparation method thereof and application of biomimetic mineralized collagen membrane in preparation of medical materials
By using a bionic mineralized collagen membrane containing hydroxyapatite, stem cell differentiation and promote the regeneration of the fibrocartilage layer of tendon bone tissue in the body, the problem of insufficient healing after tendon bone tissue injury is solved, and effective healing and mechanical recovery of tendon bone tissue is achieved.
Patent Information
- Application Number
- CN202411889292.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
After the tendon bone tissue is damaged, the lack of the healing method of the fibrocartilage layer can easily lead to scar healing and increase the risk of retearing. The prior art is difficult to effectively promote the regeneration of the fibrocartilage layer of the tendon bone tissue.
A bionic mineralized collagen membrane is provided, containing hydroxyapatite inorganic substances distributed along the long axis of collagen fibrils. Through contact with stem cells, stem cells are induced to differentiate into tendons, cartilage or bone cells, and promote the regeneration of the fibrocartilage layer of tendon bone tissue in the body.
This bionic mineralized collagen membrane can significantly promote the healing of tendon bone tissue, and restore the maximum mechanics to normal 67%, effectively reducing the risk of re-tearing.
Smart Images

Figure CN119656386A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials, and specifically relates to a bionic mineralized collagen membrane and a preparation method thereof and application of the bionic mineralized collagen membrane in the preparation of medical materials. Background Art
[0002] Tendon-bone tissue is histologically divided into three parts: tendon / ligament, fibrocartilage and bone, and plays an important role in the musculoskeletal system. The most common sites of tendon-bone tissue injury are the rotator cuff tendon of the shoulder joint and the anterior cruciate ligament of the knee joint. The incidence of rotator cuff tendon tear in the general population and people over 65 years old is approximately 20.7% and 50%, respectively. Anterior cruciate ligament tear is a common sports injury, which is more common in active young people; 1 in 3,500 people will suffer an anterior cruciate ligament injury each year. Therefore, tendon-bone tissue injury is a common musculoskeletal system disease.
[0003] Physiologically, fibrocartilage tissue can effectively transfer force from tendon to bone, thereby effectively preventing stress concentration and tendon-bone tissue tearing. Clinically, the standard practice after tendon-bone injury is to remove the fibrocartilage tissue layer on the bone surface to ensure blood seepage, and then directly connect the tendon / ligament to the bone in the absence of the fibrocartilage layer of tendon-bone tissue to initiate tendon-bone healing. However, due to the lack of the fibrocartilage layer of tendon-bone tissue, this healing is carried out in the form of tendon-bone tissue scar healing, which puts 20% to 94% of patients at risk of re-tear in clinical practice. Summary of the invention
[0004] The purpose of the present invention is to provide a biomimetic mineralized collagen membrane and a preparation method thereof and application in the preparation of medical materials. The biomimetic mineralized collagen membrane provided by the present invention can successfully induce stem cells to differentiate into tendon cells, chondrocytes or osteocytes, and can promote the regeneration of the fibrocartilage layer of tendon-bone tissue in vivo. Therefore, it is used to repair tendon-bone injuries and has significant therapeutic effects.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a biomimetic mineralized collagen membrane, comprising collagen fibrils; and inorganic substances distributed along the long axis of the collagen fibrils on the outer surface of the collagen fibrils and inside the collagen fibrils; the inorganic substances are hydroxyapatite;
[0007] The mass percentage of inorganic matter in the bionic mineralized collagen membrane is 6-62%.
[0008] Preferably, the mass percentage of inorganic matter in the bionic mineralized collagen membrane is 6-27% or 31-36% or 39-62%.
[0009] Preferably, the collagen fibrils are type I collagen fibrils.
[0010] The present invention provides a method for preparing the biomimetic mineralized collagen membrane described in the above technical solution, comprising the following steps:
[0011] Mixing the collagen hydrogel and the mineralization solution for mineralization to obtain a biomimetic mineralized collagen hydrogel, wherein the mineralization time is 1 to 6 days, and the mineralization solution contains calcium ions and phosphate ions;
[0012] The biomimetic mineralized collagen hydrogel is freeze-dried and then pressed into a film to obtain the biomimetic mineralized collagen film.
[0013] Preferably, the mineralization solution is formed by a calcium salt solution, a phosphate solution and a non-collagen mimetic; the molar concentration of calcium ions in the calcium salt solution is 1 to 4 mmol / L, the molar concentration of phosphate ions in the phosphate solution is 9 to 20 mmol / L, and the volume ratio of the calcium salt solution to the phosphate solution is 1:1.
[0014] Preferably, the non-collagen mimetic comprises polyaspartic acid, and the mass concentration of the non-collagen mimetic in the mineralization solution is 100-300 μg / mL.
[0015] Preferably, the method for preparing the collagen hydrogel comprises the following steps:
[0016] Dissolving collagen molecules in an acetic acid solution to obtain a collagen acid solution, wherein the collagen molecules are type I collagen molecules, the pH value of the acetic acid solution is 1 to 3, and the mass concentration of the collagen molecules in the collagen acid solution is ≥1 mg / mL;
[0017] The collagen acid solution is gelled under alkaline conditions to obtain the collagen hydrogel, and the gelling time is ≥20 minutes.
[0018] The present invention provides the use of the biomimetic mineralized collagen membrane described in the above technical solution or the biomimetic mineralized collagen membrane prepared by the preparation method described in the above technical solution in the preparation of medical materials.
[0019] Preferably, the medical material includes a medical material for inducing stem cells to differentiate into tendon cells, a medical material for inducing stem cells to differentiate into chondrocytes, or a medical material for inducing stem cells to differentiate into osteocytes.
[0020] The present invention provides a bionic tendon-bone tissue scaffold, comprising the bionic mineralized collagen membrane described in the above technical solution or the bionic mineralized collagen membrane prepared by the preparation method described in the above technical solution.
[0021] The present invention provides a biomimetic mineralized collagen membrane, comprising collagen fibrils; further comprising inorganic substances distributed along the long axis of the collagen fibrils on the outer surface of the collagen fibrils (external mineralization) and inside the collagen fibrils (internal mineralization); the inorganic substances are hydroxyapatite; the mass percentage of the inorganic substances in the biomimetic mineralized collagen membrane is 6-62%. The biomimetic mineralized collagen membrane provided by the present invention has an inorganic substance content of 6-62% in the membrane, and the main characteristics of the membrane structure are partially mineralized collagen fibrils (the inorganic substances and collagen fibrils distributed along the long axis of the collagen fibrils on the outer surface and inside of the collagen fibrils are partially mineralized collagen fibrils), and the inorganic substances in the membrane are hierarchically assembled from the inside of the collagen fibrils to the outer surface of the collagen fibrils (inside to outside). The biomimetic mineralized collagen membrane provided by the present invention can induce mesenchymal stem cells to differentiate into fibrocartilage cells in vitro, induce fibrocartilage tissue regeneration in vivo, promote tendon bone tissue healing, and the maximum mechanics can be restored to 67% of normal. Therefore, the bionic mineralized collagen membrane provided by the present invention is used for bionic tendon-bone tissue scaffold as a medical material for repairing tendon-bone injuries, which has great market potential.
[0022] The results of the examples show that: mesenchymal stem cells were inoculated on the biomimetic mineralized collagen membrane provided by the present invention in vitro, and after second-generation sequencing, it was found that the inorganic content of the biomimetic mineralized collagen membrane provided by the present invention was 6-27wt% which could induce stem cells to differentiate into tendon cells, 31-36wt% which could induce stem cells to differentiate into chondrocytes in vitro, and 39-62wt% which could induce stem cells to differentiate into osteocytes in vitro. The biomimetic mineralized collagen membrane provided by the present invention (inorganic content 31-36wt%) was implanted into a rat tendon-bone defect model and found that it could promote the regeneration of the fibrocartilage layer of the tendon-bone tissue in vivo, and the maximum mechanical recovery was 67% of the normal value, with significant effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Appearance information of the biomimetic mineralized collagen membrane prepared in Example ( Figure 1 left figure) and thermogravimetric analysis (n=3, Figure 1 in the right figure);
[0024] Figure 2 Transmission electron microscope (TEM) characterization image of the biomimetic mineralized collagen membrane prepared in Example;
[0025] Figure 3 The changes in tendon phenotype, cartilage phenotype and bone phenotype obtained by sequencing are shown when mesenchymal stem cells are seeded onto simple collagen to a series of biomimetic mineralized collagen membranes with inorganic content.
[0026] Figure 4 HE staining images of representative samples of tendon-bone healing areas in the blank control group and biomimetic mineralized collagen membrane group at 4 and 8 weeks after tendon-bone injury in rats;
[0027] Figure 5 These are the maximum mechanical numerical diagrams of the tendon-bone tissues in the blank control group, bionic mineralized collagen membrane group, and normal group 8 weeks after tendon-bone injury surgery in rats. DETAILED DESCRIPTION
[0028] The present invention provides a biomimetic mineralized collagen membrane, comprising collagen fibrils; and inorganic substances distributed along the long axis of the collagen fibrils on the outer surface of the collagen fibrils and inside the collagen fibrils; the inorganic substances are hydroxyapatite;
[0029] The mass percentage of inorganic matter in the bionic mineralized collagen membrane is 6-62%.
[0030] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0031] In the present invention, the biomimetic mineralized collagen membrane provided by the present invention comprises partially mineralized collagen fibrils, and the hydroxyapatite in the partially mineralized collagen fibrils is distributed on the outer surface and inside of the collagen fibrils along the long axis of the collagen fibrils.
[0032] In the present invention, the hydroxyapatite in the biomimetic mineralized collagen membrane exists in a crystalline form.
[0033] In the present invention, the mass percentage of inorganic matter in the biomimetic mineralized collagen membrane is preferably 6-27%.
[0034] In the present invention, the mass percentage of inorganic matter in the biomimetic mineralized collagen membrane is preferably 31-36%.
[0035] In the present invention, the collagen fibrils are type I collagen fibrils, that is, the partially mineralized collagen fibrils are preferably partially mineralized type I collagen fibrils.
[0036] The present invention provides a method for preparing the biomimetic mineralized collagen membrane described in the above technical solution, comprising the following steps:
[0037] Mixing the collagen hydrogel and the mineralization solution for mineralization to obtain a biomimetic mineralized collagen hydrogel, wherein the mineralization time is 1 to 6 days, and the mineralization solution contains calcium ions and phosphate ions;
[0038] The biomimetic mineralized collagen hydrogel is freeze-dried and then pressed into a film to obtain the biomimetic mineralized collagen film.
[0039] In the present invention, the method for preparing the collagen hydrogel preferably comprises the following steps:
[0040] Dissolve collagen molecules in acetic acid solution to obtain collagen acid solution. In the present invention, the collagen molecules are preferably type I collagen molecules, and the pH value of the acetic acid solution is preferably 1 to 3, specifically 3 in the embodiment. The mass concentration of collagen molecules in the collagen acid solution is preferably ≥ 1 mg / mL, more preferably 3 to 20 mg / mL.
[0041] After obtaining the collagen acid solution, the present invention gelates the collagen acid solution under alkaline conditions to obtain the collagen hydrogel. In the present invention, the gelation is carried out under room temperature, and the gelation time is preferably ≥20 minutes, more preferably 60 to 300 minutes. The pH value of the gelation is preferably 8 to 12. During the gelation process, the collagen molecules in the collagen acid solution self-assemble to form a gel. The present invention can successfully prepare a collagen hydrogel by controlling the time and pH conditions of the transaction.
[0042] In the present invention, the mineralization solution is preferably formed by a calcium salt solution, a phosphate solution and a non-collagen mimetic. The calcium salt solution is preferably the calcium salt aqueous solution. The calcium salt in the calcium salt solution is preferably CaCl2. The molar concentration of calcium ions in the calcium salt solution is preferably 1-4 mmol / L, and in the embodiment it can be 3.34 mmol / L. The phosphate solution is preferably a phosphate aqueous solution, and the phosphate solution is preferably a mixed solution of phosphate and sodium chloride, and the phosphate is preferably sodium hydrogen phosphate. The molar concentration of phosphate ions in the phosphate solution is preferably 9-20 mmol / L, and in the embodiment it can be 19 mmol / L, and the molar concentration of sodium chloride is preferably 200-400 mmol / L, and in the embodiment it can be 300 mmol / L. The volume ratio of the calcium salt solution and the phosphate solution is preferably 1:1. In the present invention, the non-collagen mimetic preferably includes polyaspartic acid, and the mass concentration of the non-collagen mimetic in the mineralization solution is preferably 100-300 μg / mL, and in the embodiment it can be 240 μg / mL. The present invention can achieve successful mineralization of collagen hydrogel by controlling the composition of the mineralization solution.
[0043] In the present invention, the method for preparing the mineralization solution preferably comprises: premixing the calcium salt solution and the non-collagen mimetic and then mixing them with the phosphate solution.
[0044] The volume ratio of the mineralization liquid to the collagen hydrogel is preferably ≥1. The present invention has no special requirements for the specific implementation process of the mineralization. The present invention obtains biomimetic mineralized collagen membranes with different inorganic contents by controlling the mineralization time. In an embodiment of the present invention, the mineralization time is 1 to 1.5 days, and a biomimetic mineralized collagen membrane with an inorganic content of 6 to 27 wt% is obtained. The mineralization time is 2 days, and a biomimetic mineralized collagen membrane with an inorganic content of 31 to 36 wt% is obtained. The mineralization time is 6 days, and a biomimetic mineralized collagen membrane with an inorganic content of 59 to 62 wt% is obtained.
[0045] After obtaining the biomimetic mineralized collagen hydrogel, the present invention freeze-dries the biomimetic mineralized collagen hydrogel and then presses it into a film to obtain the biomimetic mineralized collagen film. In the present invention, the freeze drying is carried out in a freeze dryer, and the freeze drying time is preferably 1 to 4 days. After the freeze drying, a dry product is obtained, and the present invention preferably presses the dry product into a film to obtain the biomimetic mineralized collagen film.
[0046] The present invention provides the use of the biomimetic mineralized collagen membrane described in the above technical solution or the biomimetic mineralized collagen membrane prepared by the preparation method described in the above technical solution in the preparation of medical materials.
[0047] The present invention provides the use of the biomimetic mineralized collagen membrane described in the above technical solution or the biomimetic mineralized collagen membrane prepared by the preparation method described in the above technical solution in the preparation of medical materials for repairing tendon-bone injuries, wherein the mass percentage of inorganic matter in the biomimetic mineralized collagen membrane is 31-36%.
[0048] In the present invention, the medical material preferably includes a medical material for inducing stem cells to differentiate into tenocytes, a medical material for inducing stem cells to differentiate into chondrocytes, or a medical material for inducing stem cells to differentiate into osteocytes. The above-mentioned stem cells are mesenchymal stem cells.
[0049] The present invention provides a bionic tendon bone tissue scaffold, comprising the bionic mineralized collagen membrane described in the above technical solution or the bionic mineralized collagen membrane prepared by the preparation method described in the above technical solution, wherein the mass percentage of inorganic matter in the bionic mineralized collagen membrane is preferably 31-36%.
[0050] When the mass percentage of inorganic matter in the bionic mineralized collagen membrane provided by the present invention is preferably 31-36%, the regeneration of the fibrocartilage layer of tendon bone tissue can be promoted in vivo, and the maximum mechanical recovery is 67% of the normal value.
[0051] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0052] Example 1
[0053] (1) Dissolving type I collagen molecules in an acetic acid aqueous solution at pH = 3 to obtain a type I collagen acid solution, wherein the mass concentration of type I collagen in the type I collagen acid solution is 10 mg / mL. At room temperature, the collagen acid solution is subjected to a self-assembly gelation process under alkaline conditions (pH = 11) (gelation time is 240 min) to obtain a collagen hydrogel;
[0054] (2) A calcium chloride aqueous solution (preferably the molar concentration of calcium ions is 3.34 mmol / L) and polyaspartic acid are mixed, and then mixed with a phosphate solution (preferably the molar concentration of phosphate ions is 19 mmol / L, and the molar concentration of sodium chloride is 300 mmol / L) to obtain a mineralization solution, wherein the phosphate solution is a mixed solution of sodium hydrogen phosphate and sodium chloride. The volume ratio of the calcium chloride aqueous solution to the phosphate solution is 1:1. The mass concentration of polyaspartic acid in the mineralization solution is 240 μg / mL.
[0055] The collagen hydrogel obtained in step (1) is mixed with a mineralizing solution (the volume ratio of the collagen hydrogel to the mineralizing solution is 1:1), and mineralized. After 1 to 6 days of mineralization, a biomimetic mineralized collagen hydrogel is obtained.
[0056] (3) The biomimetic mineralized collagen hydrogel obtained in step (2) is transferred to a freeze dryer, and after drying for 3 days, it is flattened into a film to obtain a biomimetic mineralized collagen film.
[0057] In this embodiment, the mineralization time is 1 to 1.5 days, and a biomimetic mineralized collagen membrane with an inorganic content of 6 to 27 wt % is obtained. The mineralization time is 2 days, and a biomimetic mineralized collagen membrane with an inorganic content of 31 to 36 wt % is obtained. The mineralization time is 6 days, and a biomimetic mineralized collagen membrane with an inorganic content of 59 to 62 wt % is obtained.
[0058] Test Example 1
[0059] Thermogravimetric analysis of the biomimetic mineralized collagen membrane with an inorganic content of 31-36 wt % prepared in Example 1 comprises the following steps:
[0060] Step S1: The sample was placed in a 37° C. oven for 3 days and subjected to thermogravimetric analysis (TGA).
[0061] Step S2: Combustion conditions: 30°C to 800°C, air;
[0062] Step S3: The mass at 660°C is analyzed as the total mass of inorganic matter;
[0063] Figure 1Characterize the appearance information of the biomimetic mineralized collagen membrane with an inorganic content of 31-36 wt % prepared in Example 1 ( Figure 1 left figure) and thermogravimetric analysis (n=3, Figure 1 (right picture in the figure). Figure 1 The right figure in the figure is a bar chart of thermogravimetric analysis. It is known that the content of inorganic matter in the biomimetic mineralized collagen membrane prepared in Example 1 is 31-36 wt % and the determined content of inorganic matter is 33 wt %.
[0064] Test Example 2
[0065] The freeze-dried type I collagen molecules were weighed and dissolved in an acetic acid aqueous solution at pH=3 to obtain a type I collagen acid solution, in which the mass concentration of type I collagen in the type I collagen acid solution was 10 mg / mL. At room temperature, the collagen acid solution was subjected to a self-assembly gelation process under alkaline conditions (pH=11) (gelation time was 240 min) to obtain a collagen hydrogel, in which the mass concentration of collagen in the collagen hydrogel was 10 mg / mL.
[0066] Step S1: Weigh 0.01 g of 10 mg / mL collagen hydrogel, put it in 1 mL of ammonium bicarbonate (PH=7.8), and grind it with a homogenizer for 16 s each time, 4 times;
[0067] Step S2: 1:2, 1:4 dilution, drop 2 μL on the nickel mesh, seal tightly with sealing film, and keep at room temperature for 3 days;
[0068] Step S3: wash with water for 2 min, 50% alcohol for 1 min, 100% alcohol for 1 min, and place in a nickel mesh box;
[0069] Step S4: TEM imaging and electron diffraction selection. Non-mineralized gel needs to be stained: 5 μL of uranyl acetate is dropped on for 10 seconds and dried in front of a baking lamp.
[0070] Figure 2 The microscopic information of the biomimetic mineralized collagen membrane was characterized by transmission electron microscopy (TEM). The images showed a large number of internal and external mineralization of collagen fibrils ( Figure 2 Left panel, scale bar: 2 μm), single fibril internal and external mineralization ( Figure 2 Selected area diffraction shows oriented crystals of hydroxyapatite with the c-axis aligned with the long axis of the collagen fibrils ( Figure 2 Inset in the right figure of the figure), yellow dashed line (inner mineralization, inside the fiber), yellow triangle (outer mineralization, outer surface of the fiber).
[0071] Depend on Figure 2 It can be seen that the inorganic matter in the interface layer exists inside and outside the collagen fibrils, the inorganic matter is in a crystalline state, and the inorganic matter inside the collagen fibrils is distributed along the long axis of the fibrils.
[0072] Test Example 3
[0073] Step S1: Mesenchymal stem cells were seeded on the mineralized hydrogel, and after induced differentiation for 3 days, RNA was extracted according to the instructions of the RNA Rapid Extraction Kit (Shanghai Yishan Biotechnology Co., Ltd.);
[0074] Step S2: RNA samples were sent on dry ice to BGI (Wuhan) for sequencing analysis;
[0075] Step S3: Tendon phenotype, cartilage phenotype and bone phenotype genes were selected respectively, and the gene expression changes from simple collagen to a series of bionic mineralized collagen membranes with inorganic content were compared. It was found that the inorganic content of 6-27% can induce stem cells to differentiate into tendon cells, 31-36% can induce stem cells to differentiate into chondrocytes in vitro, and 39-62% can induce stem cells to differentiate into osteocytes in vitro.
[0076] Figure 3 The changes in tendon, cartilage and bone phenotypes obtained by sequencing were characterized by mesenchymal stem cells seeded on simple collagen to a series of inorganic content biomimetic mineralized collagen membranes. Figure 3 The results show that the bionic mineralized collagen membrane with an inorganic content of 6-27% can induce stem cells to differentiate into tendon cells, the bionic mineralized collagen membrane with an inorganic content of 31-36% can induce stem cells to differentiate into chondrocytes in vitro, and the bionic mineralized collagen membrane with an inorganic content of 39-62% can induce stem cells to differentiate into osteocytes in vitro.
[0077] Test Example 4
[0078] Step S1: The patella-patellar ligament is removed, and the tissue is fixed, decalcified, dehydrated, transparent, wax-impregnated, and embedded, and the slice thickness is 7 μm.
[0079] Step S2: Hematoxylin-eosin staining: paraffin sections were baked, dewaxed, hydrated with gradient alcohol to double distilled water, stained with hematoxylin for 12 min, separated with 1% hydrochloric acid, washed twice with water, stained with eosin for 15 s, washed twice with water, decolorized with gradient alcohol, made transparent, and sealed.
[0080] Figure 4 HE staining images of representative samples of the tendon-bone healing area in the blank control group and the biomimetic mineralized collagen membrane (inorganic content 31-36wt%) group were characterized 4 and 8 weeks after tendon-bone injury surgery in rats. It was found that at 4 weeks after surgery, fibrocartilage tissue regeneration was observed in the biomimetic mineralized collagen membrane group compared with the blank control group (the black dotted line represents the regenerated fibrocartilage tissue).
[0081] Test Example 5
[0082] Step S1: Collect the quadriceps-patella-patellar ligament complex, record the width and thickness of the tendon-bone junction, and fix the complex on the fixture;
[0083] Step S2: 0.1N load, elongation within 0.5mm, 5mm / min, after the composite is treated for 20 cycles, enter the load-fracture test (5mm / min);
[0084] Step S3: Record the maximum pulling force (N)
[0085] Figure 5 The maximum mechanical values of the tendon-bone tissues in the blank control group, bionic mineralized collagen membrane group, and normal group were characterized 8 weeks after tendon-bone injury surgery in rats. Figure 5 It was shown that implanting a bionic mineralized collagen membrane with an inorganic content of 31-36wt% into a rat tendon-bone defect model could promote the regeneration of the fibrocartilage layer of the tendon-bone tissue in vivo, and the maximum mechanical properties were restored to 67% of normal.
[0086] From the above examples, it can be seen that the biomimetic mineralized collagen membrane provided by the present invention has an inorganic content of 6 to 62% in the membrane, and the main feature of the membrane structure is partially mineralized collagen fibrils (the inorganic matter distributed on the outer surface and inside of the collagen fibrils along the long axis of the collagen fibrils is the partially mineralized collagen fibrils), and the inorganic matter in the membrane is hierarchically assembled from the inside of the collagen fibrils to the outer surface of the fibers (inside to outside). The biomimetic mineralized collagen membrane provided by the present invention can induce mesenchymal stem cells to differentiate into fibrocartilage cells in vitro, induce fibrocartilage tissue regeneration in vivo, promote tendon-bone tissue healing, and the maximum mechanics can be restored to 67% of normal. Therefore, the biomimetic mineralized collagen membrane provided by the present invention is used for biomimetic tendon-bone tissue scaffolds as medical materials for repairing tendon-bone injuries, and has great market potential.
[0087] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A biomimetic mineralized collagen membrane, characterized in that: It includes collagen fibrils; and also includes inorganic substances distributed on the outer surface of the collagen fibrils and inside the collagen fibrils along the long axis of the collagen fibrils; the inorganic substances are hydroxyapatite; The mass percentage of inorganic matter in the bionic mineralized collagen membrane is 6-62%.
2. The biomimetic mineralized collagen membrane according to claim 1, characterized in that: The mass percentage of inorganic matter in the bionic mineralized collagen membrane is 6-27% or 31-36% or 39-62%.
3. The biomimetic mineralized collagen membrane according to claim 1 or 2, characterized in that: The collagen fibrils are type I collagen fibrils.
4. The method for preparing the biomimetic mineralized collagen membrane according to any one of claims 1 to 3, characterized in that: The following steps are involved: Mixing the collagen hydrogel and the mineralization solution for mineralization to obtain a biomimetic mineralized collagen hydrogel, wherein the mineralization time is 1 to 6 days, and the mineralization solution contains calcium ions and phosphate ions; The biomimetic mineralized collagen hydrogel is freeze-dried and then pressed into a film to obtain the biomimetic mineralized collagen film.
5. The preparation method according to claim 4, characterized in that: The mineralization solution is formed by a calcium salt solution, a phosphate solution and a non-collagen mimetic; the molar concentration of calcium ions in the calcium salt solution is 1 to 4 mmol / L, the molar concentration of phosphate ions in the phosphate solution is 9 to 20 mmol / L, and the volume ratio of the calcium salt solution to the phosphate solution is 1:
1.
6. The preparation method according to claim 5, characterized in that: The non-collagen mimic includes polyaspartic acid, and the mass concentration of the non-collagen mimic in the mineralization solution is 100-300 μg / mL.
7. The preparation method according to claim 4, characterized in that: The preparation method of the collagen hydrogel comprises the following steps: Dissolving collagen molecules in an acetic acid solution to obtain a collagen acid solution, wherein the collagen molecules are type I collagen molecules, the pH value of the acetic acid solution is 1 to 3, and the mass concentration of the collagen molecules in the collagen acid solution is ≥1 mg / mL; The collagen acid solution is gelled under alkaline conditions to obtain the collagen hydrogel, and the gelling time is ≥20 minutes.
8. Use of the biomimetic mineralized collagen membrane according to any one of claims 1 to 3 or the biomimetic mineralized collagen membrane prepared by the preparation method according to any one of claims 4 to 7 in the preparation of medical materials.
9. The use according to claim 8, characterized in that: The medical material includes a medical material for inducing stem cells to differentiate into tendon cells, a medical material for inducing stem cells to differentiate into chondrocytes, or a medical material for inducing stem cells to differentiate into osteocytes.
10. A bionic tendon-bone tissue scaffold, characterized in that: The invention comprises the biomimetic mineralized collagen membrane according to any one of claims 1 to 3 or the biomimetic mineralized collagen membrane prepared by the preparation method according to any one of claims 4 to 7.